2020
DOI: 10.1016/j.sdentj.2019.11.003
|View full text |Cite
|
Sign up to set email alerts
|

Dental Caries Experience and Oral Health Related Quality of Life in Working Adults

Abstract: Objective To evaluate effect of dental caries experience and untreated dental decay on Oral Health-Related Quality of Life (OHRQoL) in working adults. Methods The clinical records of 160 patients were reviewed. Dental health indicators were derived from individual tooth- and surface-level data allowing for calculating the number of decayed surfaces (D), number of decayed missed filled surfaces (DMFS), and significant caries (SiC) indices. A questionnaire was administere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
18
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 38 publications
6
18
0
3
Order By: Relevance
“…In the present study, the interviewees who had three or more visible cavities (48; 18.18%) also presented data that suggested a lower quality of life compared to those with less than three cavities, with a statistically significant difference of p<0.001. This finding is supported by studies carried out in Makkah city, Saudi Arabia [28], where adults with higher caries experience presented lower quality of life.…”
Section: Discussionsupporting
confidence: 64%
“…In the present study, the interviewees who had three or more visible cavities (48; 18.18%) also presented data that suggested a lower quality of life compared to those with less than three cavities, with a statistically significant difference of p<0.001. This finding is supported by studies carried out in Makkah city, Saudi Arabia [28], where adults with higher caries experience presented lower quality of life.…”
Section: Discussionsupporting
confidence: 64%
“…Significant caries (SiC) and decayed missed filled surfaces (DMFS) indices were used as dental health indicators. The results indicated that the SiC score could statistically significantly predict the OHIP score [ 17 ].…”
Section: Reviewmentioning
confidence: 99%
“…There are several studies that reported that the dental caries have negative impacts on OHRQoL in populations of different ages [16][17][18]. The effect of dental caries experience and untreated dental decay and on OHRQoL was examined in working adults.…”
Section: Introductionmentioning
confidence: 99%
“…Dental caries is one of the most prevalent chronic diseases and the most common oral condition worldwide and is considered the main indicator of oral health (Dye et al 2012;Bukhari 2020). This is a disease where multiple factors act together in highly complex processes and cause the bacterial community to change in balance to a dysbiotic community.…”
Section: Introductionmentioning
confidence: 99%